2004
DOI: 10.1093/oxfordjournals.schbul.a007089
|View full text |Cite
|
Sign up to set email alerts
|

Left Prefrontal Repetitive Transcranial Magnetic Stimulation in Schizophrenia

Abstract: In a double-blind, controlled study, we examined the therapeutic effects of high-frequency left prefrontal repetitive transcranial magnetic stimulation (rTMS) on schizophrenia symptoms. A total of 22 chronic hospitalized schizophrenia patients were randomly assigned to 2 weeks (10 sessions) of real or sham rTMS. rTMS was given with the following parameters: 20 trains of 5-second 10-Hz stimulation at 100 percent motor threshold, 30 seconds apart. Effects on positive and negative symptoms, self-reported symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 20 publications
2
51
0
3
Order By: Relevance
“…This was underlined by a study which reported a significant improvement in negative symptoms in 20 schizophrenic patients treated with 10 Hz high-frequency rTMS compared to sham stimulation (Hajak et al 2004). In contrast to these encouraging results, a recently published study showed no significant effect of 10 Hz rTMS over left dorsolateral prefrontal cortex in 22 chronically hospitalised schizophrenic patients compared to sham (Holi 2004). The severity of disease and dosage of medication were discussed as possible explanations for the missing effect.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…This was underlined by a study which reported a significant improvement in negative symptoms in 20 schizophrenic patients treated with 10 Hz high-frequency rTMS compared to sham stimulation (Hajak et al 2004). In contrast to these encouraging results, a recently published study showed no significant effect of 10 Hz rTMS over left dorsolateral prefrontal cortex in 22 chronically hospitalised schizophrenic patients compared to sham (Holi 2004). The severity of disease and dosage of medication were discussed as possible explanations for the missing effect.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…Cordes et al [20], found mild to moderate effect using 10 Hz stimulation at 110 % MT in a sham-controlled trial of 35 individuals with chronic schizophrenia. In a group of 22 chronic, hospitalized patients with schizophrenia, high-frequency TMS was not found to have a therapeutic effect [21]. Novak et al [22], were unable to show that high-frequency rTMS over the left DLPFC would decrease negative symptoms in 16 patients with schizophrenia.…”
Section: Effect Of Rtms On Negative Symptomsmentioning
confidence: 97%
“…Therefore, in neuropsychiatric disorders where particular brain regions or networks exhibit diminished activity, anodal stimulation would be used to increase activity in these hypofunctioning regions. Conversely, cathodal stimulation could modulate hyperactive regions [65][66][67][68].…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%